Association of albumin or protamine to lipoplexes: enhancement of transfection and resistance to serum - Faneca, H. (2004)
The successful application of gene therapy depends on the availability of carriers to efficiently deliver genetic material into target cells. Such efficacy is strongly related to key parameters including serum resistance and protection of DNA.The complexes were tested in terms of their biological activity, in the absence or presence of serum, by following transfection activity. Interaction with plasma proteins was evaluated by immunoblotting, while cytotoxicity was assessed by the Alamar Blue assay. Extent of DNA protection was determined both by using ethidium bromide intercalation and DNase I digestion assays.Our results show that, depending on the charge ratio and on the lipid composition, albumin and protamine can be used (either individually or co-associated) to generate cationic liposome/DNA complexes fulfilling in vivo requirements, while exhibiting high levels of transfection activity. In the present work a novel cationic lipid was tested. It was demonstrated that 1-palmitoyl-2-oleoyl-sn-glycero-3-ethylphosphocholine (EPOPC):cholesterol (Chol) liposomes constitute a very promising carrier for gene delivery as illustrated by their enhancing effect on transfection, as compared with DOTAP-containing liposomes. Moreover, the biological activity of EPOPC-containing complexes is significantly improved upon association of albumin, even in the presence of 60% serum (namely for the 4/1 lipid/DNA charge ratio). Nevertheless, our studies also show that transfection activity mediated by DOTAP-containing complexes can be significantly enhanced upon pre-condensation of DNA with protamine.Co-association of HSA and protamine to lipoplexes ensures a high degree of DNA protection and results in high levels of transfection activity even in the presence of serum. Copyright © 2004 John Wiley & Sons, Ltd.